Modern software engineering concepts and practices : advanced approaches - Dogru, Ali H., 1957-; Bicar, Veli, 1980- (Hershey, PA : Information Science Reference, 2011)
"This book provides emerging theoretical approaches and their practices and includes case studies and real-world practices within a range of advanced approaches to reflect various perspectives in the discipline"--Provided by publisher.
Includes bibliographical references (p. 416-457) and index.
Keywords: Software engineering